Vector Magnetic Fields of A Solar Polar Region - Jin, Chunlan; Wang, Jingxiu (The Astrophysical journal, 2011)
We study the vector magnetic fields of a solar polar region (PR) based on Solar Optical Telescope/Spectro-Polarimeter measurements. To better understand the polar magnetic properties, we compare the observed polar field with that in two solar quiet regions at the limb (QRL) and the disk center (QRD), and with that in a region of a low-latitude coronal hole (CHR). The following results are discussed: (1) The average vertical flux density of PR is 16 G, while the average horizontal flux density is 91 G. If we assume that the observed polar field suffers the same amount of limb weakening in polarization measurements as the Sun's quiet region, the average unsigned flux density in the pole would be 54 G, 60% stronger than that in the CHR. (2) The kG field in the PR occupies 6.7% of the region. The magnetic filling factor in the PR is characterized by a two-peak distribution, which appears at a field strength close to 100 G and 1000 G, respectively. (3) For the network elements, a correlation holds between the vertical and horizontal flux densities, suggesting the same physical entity is manifested by the observed stronger vertical and horizontal components. (4) The ratio of the magnetic flux in the minority polarity to that in the dominant polarity is approximately 0.5, implying that only 1/3 of the magnetic flux in the PR opens to the interplanetary space. Exemplified with CHR by a quasi-linear force-free extrapolation of the observed magnetic field, we find that the photospheric open flux is not always associated with strong vertical magnetic elements.